Stereotactic Ablative Body Radiotherapy for Lung Metastases: Where is the Evidence and What are We Doing With It? - Siva, Shankar; Slotman, Ben J. (Seminars in radiation oncology, 2017)
This review provides an overview of the use of stereotactic ablative body radiotherapy (SABR) for pulmonary metastases. The local control rates after SABR are generally >90%. Whether this also translates into a significant improvement in overall survival is the subject of ongoing studies. New exciting opportunities including the integration of SABR with targeted and immune therapies as well as some competing treatment strategies are discussed.